2019
DOI: 10.11143/fennia.70337
|View full text |Cite
|
Sign up to set email alerts
|

Life satisfaction among inbound university students in northern Sweden

Abstract: Will life satisfaction among international students change after having an experience of studying abroad? Some previous studies indicate inequalities and issues of social mobility embedded in international student mobility. International student mobility implies physical movement and new experiences gained while studying abroad. The ubiquity of international students and their generally successful adaptation makes it necessary to understand how they manage to turn a seemingly difficult situation into satisfying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Some scholars have focused on positive adjustment among international students to a new study system. Nilsson and Stålnacke's findings suggested that the inbound students had a marginally higher level of satisfaction with their study situation [11]. Therefore, satisfaction can be a useful indicator to evaluate international students' campus life.…”
Section: Level Of Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some scholars have focused on positive adjustment among international students to a new study system. Nilsson and Stålnacke's findings suggested that the inbound students had a marginally higher level of satisfaction with their study situation [11]. Therefore, satisfaction can be a useful indicator to evaluate international students' campus life.…”
Section: Level Of Satisfactionmentioning
confidence: 99%
“…It requires a degree of personal judgment to determine whether one's aspirations have been achieved [42]. Life satisfaction may involve one's academic situation, finances, daily life, partnership, and somatic and psychological health [11]. Moreover, previous studies have indicated life satisfaction is a significant indicator to evaluate how well international students have adjusted to their new studying situation [43,44].…”
Section: Level Of Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers enhance research novelty by utilizing the latest scientific advancements. The concept of cultural adaptation has been widely explored in various scientific fields, as demonstrated by Bashir et al (2021), Beaven and Spencer-Oatey (2016), Brown et al (2016), V. Chirkov et al (2007), Di Pietro (2015), King and Sondhi (2018), Le Huu Nghia (2019), Nilsson and Stålnacke (2019), Peng et al (2015), and Yang et al (2018). Their research indicates that students who study independently exhibit high adaptability.…”
Section: Introductionmentioning
confidence: 99%
“…This study took Taiwan as an example to explore the decisions of international students and their views on learning during the COVID-19 pandemic. The design of the study was different from a previous single institute survey of non-degree exchange students [11,12]. We considered degree-seeking students, with differences in institutes and the students' countries of origin, based on push-pull theory and the institutional situation.…”
Section: Introductionmentioning
confidence: 99%